KERANGKA KONSEPTUAL PENDIDIKAN MATEMATIKA REALISTIK PADA KELAS VIRTUAL UNTUK MENINGKATKAN KEMAMPUAN PEMODELAN MATEMATIKA SISWA SMP - Chairunisah Chairunisah (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract : Conceptual Framework of Realistic Mathematics Education in Virtual Classrooms to Improve Mathematical Modeling Ability of Junior High School Students. The main objective of this research is to develop a virtual classroom with a realistic mathematics education (RME) approach in junior high schools. This approach helps and improves student learning achievement with good student mathematical modeling skills. Instructional design with a realistic mathematical education is integrated into a virtual classroom in collaboration with the classroom environment. The results of this study indicated (1) that the virtual classroom environment through this approach was effective in terms of classical completeness, achievement of learning time, and achievement of learning objectives, (2) students' mathematical modeling abilities through virtual classes by strengthening the learning process of realistic mathematics was increasing. The result showed that students can solve the mathematics problem supported by the help of information technology such as media assistance both formal and informal communication. Realistic mathematics education encourages students to learn collaboratively and participate in building instincts, reasoning and individual mathematical modeling skills.Keywords : Virtual Classroom, Realistic Mathematics Education, Mathematics Modelling AbilityAbstrak : Kerangka Konseptual Pendidikan Matematika Realistik pada Kelas Virtual untuk Meningkatkan Kemampuan Pemodelan Matematika Siswa SMP. Tujuan utama dari penelitian ini adalah mengembangkan kelas virtual dengan pendekatan pembelajaran matematika realistik (PMR) di sekolah. Pendekatan ini membantu dan meningkatkan hasil belajar siswa dengan kemampuan pemodelan matematika siswa yang baik. Desain instruksional dengan pendekatan matematika realistik diintegrasikan ke dalam kelas virtual yang dikolaborasikan dengan lingkungan kelas. Hasil penelitian ini menunjukkan (1) bahwa lingkungan kelas virtual melalui pendekatan ini efektif dikembangkan ditinjau dari ketuntasan klasikal, ketercapaian waktu pembelajaran, dan ketercapaian tujuan pembelarajan, (2) kemampuan pemodelan matematika siswa melalui kelas virtual dengan penguatan proses pendekatan matematika realistik meningkat. Hasil penelitian menunjukkan bahwa siswa dapat menyelesaikan masalah matematika yang didukung dengan bantuan teknologi informasi seperti bantuan media komunikasi baik formal maupun informal. Sedangkan pendekatan matematika realistik mendorong siswa untuk belajar secara berkolaborasi dan berpartisipasi dalam membangun naluri, daya nalar dan keterampilan memodelkan matematika secara individual.Kata kunci : Kelas Virtual, Pendekatan Matematika Realistik, Kemampuan Pemodelan Matematika